2010
DOI: 10.1007/s11664-010-1156-x
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence Study of InP Photonic Structures Fabricated by Dry Etching

Abstract: International audienceRidge waveguides fabricated by inductively coupled plasma (ICP) etching using chlorine-based gases were studied by spectrum image cathodoluminescence (CL). Structures with different dimensions (height and width) were studied, evidencing the generation of defects during ICP processing. Using the CL spectrum images, the distribution of the stresses induced by the defects was mapped. The residual stresses depend on the dimensions of the waveguides. Using finite-element analysis the strain di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The apparent discontinuity at the ridge edges is not an artefact. It arises from the fact that the scanned region inside the ridge lies near the top surface, whereas it lies near the bottom etched surface outside the ridge 25 . The etch depth (3 µm) is much larger than the depth probed in InP by the 5 kV electron beam in the CL measurement.…”
Section: Spectral Shift Cathodoluminescence (Ss-cl)mentioning
confidence: 99%
“…The apparent discontinuity at the ridge edges is not an artefact. It arises from the fact that the scanned region inside the ridge lies near the top surface, whereas it lies near the bottom etched surface outside the ridge 25 . The etch depth (3 µm) is much larger than the depth probed in InP by the 5 kV electron beam in the CL measurement.…”
Section: Spectral Shift Cathodoluminescence (Ss-cl)mentioning
confidence: 99%
“…Strain in light emitting semiconductors can also be assessed using photoluminescence (PL) 6,14 or cathodoluminescence (CL) [15][16][17][18][19][20] spectroscopy. In these techniques, the hydrostatic component of the deformation is given by the spectral shift due to electronic transitions through the material's bandgap.…”
Section: Introductionmentioning
confidence: 99%
“…20 The strain fields induced by the HM are well known and have been modelized. 20 Etched InP samples have also been characterized by CL spectroscopy 18,19 and DOP of PL 19 although in the top view only. Etching is suspected to introduce stress within the patterned lines.…”
Section: Introductionmentioning
confidence: 99%
“…Berrier et al [1] studied the effect of dry etching conditions on carrier lifetime reduction in InAsGaP quantum wells (QWs) in InP-based photonic crystal structures. In early studies, using cathodo-luminescence (CL) spectral imaging, we have looked at the effects of dry etching on the spectroscopic properties of rectangular ridge waveguides etched in InP or QW structures on InP ( [2,3]). It was shown that mechanical stress is induced in such structures following the dry etching.…”
Section: Introductionmentioning
confidence: 99%